Modal Intelektual Islam dan Ukuran Perbankan terhadap Kinerja Maqashid Syariah - Yusro Rahma; Atiqah Atiqah (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
The high level of public trust in the growth of the world of Islamic banking makes Islamic banking have to think about changing strategies based on Islamic intellectual capital and performance based on Islamic maqashid with the role and size of banking as a strong supporter. This research aims to examine that Islamic Intelectual Capital (IIC) and size of banking influence toward Maqashid Syariah Performance (MSP). This research used a sample of Islamic banking in Indonesia listed in the FSA the period 2014 to 2018. Methods using moderated regression analysis. The results of this research prove that Islamic Banking Value Added of Human Capital (IBVAHU) has negative effect toward MSP at significance level 10%. Islamic Banking Value Added of Capital Employed (IBVACA) and Islamic Banking Value Added of Structure Capital (IBSTVA) have not effect as partially toward of MSP. Size of banking has not effect toward Maqashid Syariah Performance (MSP). Size of banking cannot moderate relationship between IBVACA and IBSTVA toward of MSP. But Size of banking can moderate relationship between Islamic Banking Value Added of Human Capital (IBVAHU) toward of MSP.How to Cite:Rahma, Y., & Atiqah. (2021). Modal Intelektual Islam dan Ukuran Perbankan Terhadap Kinerja Maqashid Syariah. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 201-214.